2017
DOI: 10.1080/13636820.2016.1269359
|View full text |Cite
|
Sign up to set email alerts
|

Higher vocational education and social mobility: educational participation in Australia and England

Abstract: This article explores the issue of social mobility in relation to the recent expansion of higher vocational education by non-university providers. The post-school vocational education sector has become the object of policies to widen access to higher education to ensure greater social mobility and provide second chance education to those who do not complete initial education in Anglophone countries. Drawing on typologies of vocational education and training systems, the article generates understanding of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 43 publications
1
22
0
2
Order By: Relevance
“…The themes appeared to highlight a new type of social identity that the university, through its seven colleges, was adopting in line with Hogg's (2016) and West's (2014) notion of transformative learning via social identity. The reports suggested that the university appeared to adopt a moral anchor in its education provision as part of their new identity development (Nakabugo & Siebörger, 2001) and in recognition of the need to act for society's benefit when the latter has been challenged by a complex range of socio-political factors as highlighted by Webb et al (2017) and Msila and Gumbo (2016).…”
Section: Resultsmentioning
confidence: 99%
“…The themes appeared to highlight a new type of social identity that the university, through its seven colleges, was adopting in line with Hogg's (2016) and West's (2014) notion of transformative learning via social identity. The reports suggested that the university appeared to adopt a moral anchor in its education provision as part of their new identity development (Nakabugo & Siebörger, 2001) and in recognition of the need to act for society's benefit when the latter has been challenged by a complex range of socio-political factors as highlighted by Webb et al (2017) and Msila and Gumbo (2016).…”
Section: Resultsmentioning
confidence: 99%
“…I believe this may be characterised as a break with the historically strong class compromise maintained by longstanding Social Democratic rule and the Swedish model (Hickox & Lyon, 1998). The implications for students' possibilities of occupational and social mobility, which has also been a topic for discussion within other national systems of higher or continuing VET (e.g., Bathmaker, 2017;Webb, Bathmaker, et al, 2017;Webb, Burke, et al, 2017) is deeply problematic from the perspective of this thesis as it values education and access to knowledge as a means for democratic inclusion (Marginson, 2016;Nylund et al, 2017;Wheelahan, 2007).…”
Section: Decentralised Organisation Of Education and Knowledgementioning
confidence: 93%
“…For articles 2 and 3 (J. Köpsén, 2020bKöpsén, , 2020d which focus on curriculum and the knowledge in HVE it is foremost the typologies, discussions and previous studies presented in the sections 'Different approaches to knowledge in VET' and 'Employers and the knowledge in curricula' that have been used (e.g., Avis, 2012;Brockmann et al, 2008;Gamble, 2014;Nylund & Rosvall, 2016;Nylund et al, 2017;Wheelahan, 2007Wheelahan, , 2009Young, 2006Young, , 2013 but also research that pose critical questions of whether the expanded access to, and vocational pathways in, higher education actually are contributing to reducing inequalities play a crucial part of the backdrop for these articles (e.g., Bathmaker, 2017;Marginson, 2016;Webb, Bathmaker, et al, 2017;Webb, Burke, et al, 2017).…”
Section: Conclusion: Use Of the Research In This Reviewmentioning
confidence: 99%
“…Whilst others have argued that whilst this may be the case, the type of higher education that these students are participating in is low-status with very few opportunities for increased earnings or social mobility (Avis & Orr, 2016). The policy assumption that increased qualifications will lead to increased upward social mobility has been critiqued on the basis that as educational systems expand and diversify, qualifications within them are revalued (Webb et al, 2017). However, whilst HIVE qualifications may not benefit individuals in terms of social mobility they do offer an opportunity of increased access to the broader benefits of participation in HE and the knowledge that participants are likely to be exposed to.…”
Section: Degrees In Vocational Institutions -The English Contextmentioning
confidence: 99%